Nutrient resorption efficiency of cocoa plantson lowl and of Alluvial plain - Rudy Erwiyono; A. Adi Prawoto; A.S. Murdiyati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
Observation on nutrient retranslocation of cocoa plants has been carried out in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute (ICCRI) in Jember in order to assess its efficiency to have better understanding on the loss of nutrients through cocoa litterfall relatively intensive during dry season, better utilization of the plant litters, and further more efficient plant management. Nutrient retranslocation assessment has been conducted for macro nutrients in terms of N, P, and K that have been observed on four clones of cocoa planted in 2004, that are KW 163, KW 162, KKM 22, and KW 165 in the plot with Tectona grandis shading trees and plot with Cassia surithensis shading trees, with five replicates. The plots of observation overlaid on Alluvial plain 45 m asl. and D type rainfall. The results showed that nutrient contents in senescence leaves with yellow colour and then falling significantly lower than those of mature leaves with green colour adjacent to it. Reductions of N, P, and K contents during leaf senescence occured significantly on KW 163, KW 162, and KKM 22 clones, whereas on KW 165 clone significant reduction only happened to phosphorus. Mature leaves of cocoa with green colour contained average nitrogen, phosphorus, and kalium at 13.0, 1.6, and 13.5 mg/g- respectively. Whereas senescing leaves with yellow colour then defoliating contained average nitrogen, phosphorus, and kalium at 9.5, 0.9, and 10.0 mg/g, respectively. This reduction of nutrient contents was caused by nutrient retranslocation mechanism of the plants. Nitrogen, phosphorus, and kalium retranslocated by cocoa plants in rainy season are as much as 3.60, 0.70, and 3.39 mg/g, or 27%, 42%, and 24%, respectively. In other words nutrient retranslocation efficiency of cocoa plants for N, P, and K is in the following order: P>N>K. Among the clones, KKM 22 clone retranslocated P and K most efficiently; whereas for N, KW 162 clone retranslocated it most efficiently. As such, cocoa leaf litters still contained N, P, and K nutrients as much as 73%, 58%, and 76%, they are good sources for nutrients beside as organic matter. Key words: Nutrient retranslocation, nitrogen, phosphorus, kalium, cocoa, clone.